Legal Consequences Of Decision To Refuse Marriage/Isbat Nikah On Marriage Status And Child Status (Case Study of Pasuruan Religious Court Decision Number: 0360/Pdt.P/2022/PA.Pas) - Hidayati, Ammalia; Muhibbin, Moh; Suratman, Suratman (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
The rise of cases requesting validation/itsbat nikah at the Pasuruan Religious Court signals that there are still many people who are less or not even aware of the importance of marriage registration at the Office of Religious Affairs (KUA). The research method used is normative legal research, using statutory, conceptual, and case approaches. The result of this study is the consideration of the Panel of Judges in deciding case number 0360/Pdt.P/2022/PA.Pas related to the decision to reject the marriage validation/itsbat nikah case against the ratio decedendi and the legal consequences for the wife and child is that the formal requirements carried out by both parties are not fulfilled. So that the legal consequences related to the rejection of the application for itsbat nikah by the judge against unregistered siri marriage are losses for the wife and children, including: difficulty obtaining the right to maintenance, joint property in the event of a divorce or the right to inheritance if the husband dies, the child will also find it difficult to get recognition from his father in the birth certificate.